How do different executive function components contribute to children's academic skills? - He, Jiao; Xu, Rongke; Yang, Yang; Van Hoof, Jo; Yang, Xiujie (Elsevier, 2025)
This study investigated the extent to which components of executive function (EF)-working memory, inhibitory control, and cognitive flexibility-accounted for the unique variance in reading ability, arithmetic skills, and word problem solving, while considering the interplay among these academic abilities. While most of the research in this field has been conducted in Western countries, this study extends the literature by focusing on Chinese students. One hundred and eighteen Chinese children completed assessments in working memory (Sequential whack-amole task), inhibitory control (Go/No-Go task), cognitive flexibility (Task-switching), reading (reading fluency), and mathematics (numerical operations and word problem solving). The findings, derived from a multivariate multiple regression model, revealed that working memory was a significant predictor of all three academic abilities. Inhibitory control played as a substantial role in predicting reading ability and arithmetic skills. In contrast, cognitive flexibility did not show a significant relationship with any of these academic abilities. The results emphasize that not three components of EF are equally important in explaining variance in these academic skills among Chinese children.